Dementia Competence Network. Results and outlook - Peters, Oliver; Heuser, Isabella; Froelich, Lutz; Ruether, Eckart; Rienhoff, Otto; Kornhuber, Johannes; Wiltfang, Jens; Maier, Wolfgang (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
The Dementia Competence Network (DCN) is represented by academic memory clinics and has three major aims: (1) To facilitate the development of diagnostic tools including neuropsychology, biomarkers, imaging and genetics. (2) To implement clinical trials in mild cognitive impairment and dementia and (3) to improve standard care for dementia in Germany.This article summarizes the achievements of the DCN so far and highlights future perspectives.The DCN has built up two multicentre cohorts. Within the first cohort, patients with mild cognitive impairment or mild dementia were examined longitudinally using multiple neuropsychological assessments and numerous different biomarkers. In a subgroup of the first cohort, patients were treated with antidementive drugs in two placebo-controlled clinical trials. The second cohort included cognitively healthy older people and examined repetitively clinical, neuropsychological and psychosocial parameters for ten years.The DCN has generated a large data and biomaterial bank. Numerous publications have helped to develop further diagnostic procedures and treatment of cognitive disorders and dementia. The DCN has contributed to end stigmatisation of dementia.
EVALuna2:23785